Ukraina Sitši küttide leegion (1914–1918) [The Legion of Ukrainian Sich Riflemen in 1914–1918] - Martsenjuk, Ruslana (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2018)
This article is devoted to the sole Ukrainian national military unit that existed in World War I, namely the Legion of Ukrainian Sich Riflemen. It was founded in August 1914 within the Austro-Hungarian Armed Forces as Th e Imperial and Royal Ukrainian Volunteer Legion, being a part of the Austrian Territorial Army (Landwehr). Th e creation of the Legion was initiated by the Supreme Ukrainian Council, the national steering body, composed of infl uential Ukrainian politicians, public figures and activists. Th ere were 28,000 volunteers altogether, young women among them, who responded to the appeal of the Council and gathered in Lviv in the first days of the war. Most of them were members of various Ukrainian paramilitary and sport organizations which maintained old Cossack traditions.Austrian military authorities limited the strength of the Legion to 2,500 men. In September 1914, the newly recruited soldiers pledged their allegiance not only to Austria but also to Ukraine. Aft er that the Legion was deployed to the Transcarpathian region, where training was completed and the Legion was sent to the front in spring 1915. The Legion participated in the liquidation of the Russian breakthrough near Berezhany on 2 November 1915. In the battle on the slopes of the Lysonia hill more than a thousand Ukrainian rifl emen were killed, wounded or taken prisoner by the Russian forces.In summer 1916, during the Russian main off ensive commanded by General Alexei Brusilov, the Legion defended its positions during two months along the hill path between Pidhaitsi and Berezhany and was surrounded. One hundred and fifty Ukrainians were killed in action and 1,000 taken prisoner.In February 1917, the Legion returned to the trenches near Berezhany. After the February revolution in Russia and the fall of the Russian Monarchy the hostilities ceased for a while. The legionaries fraternized with Ukrainian soldiers in the Russian army. In summer, the Russian Provisional Government under pressure from the Allies launched a new offensive. At the end of June 1917, the Legion entered a fi erce battle near the village of Koniukhy. As a result almost a half of approximately 1,000 riflemen were killed or captured by the enemy. Later, the remains of the Legion, along with soldiers from its reserve and replenishment unit, participated in the counteroff ensive of German and Austrian troops. On their way to the Zbruch river the legionaries took bloody revenge, capturing the town of Kozova.In February 1918, the Ukrainian People’s Republic was established and signed a peace treaty with Germany and other Central Powers. German and Austrian troops occupied Ukraine and drove the Bolsheviks out. Th e Legion also participated in the occupation. Riflemen were deployed near the city of Oleksandrivsk (modern day Zaporizhia), where they stayed until the end of the Great War. Aft er the disintegration of Austria-Hungary, the Legion became the regular military unit of the West Ukrainian People’s Republic, proclaimed in November 1918. Former legionaries participated in the Polish-Ukrainian War and suffered heavy losses. Finally, on 2 May 1920, the unit was disbanded.